Challenges of Muhammadiyah’s Contribution in Handling Covid-19 in The MCCC Program in Indonesia - Nurul Humaidi; Rani Darmayanti; Rahmad Sugianto (Khazanah Sosial, 2022)
This study aims to describe the contribution of Muhammadiyah in the formation of the Muhammadiyah Covid-19 Command Center (MCCC) Program as a response to the COVID-19 outbreak. The research method used in this study is library research using historical methods by reviewing research on the Muhammadiyah MCCC program related to (1) what contributions have been made, (2) what challenges have been experienced in its implementation, and (3) solutions for the COVID-19 outbreak. Data collection was carried out using research on (1) the MCCC program, (2) the covid-19 pandemic, (3) the response of Muhammadiyah in the social and health fields, (4) da'wah. The results of the study that Muhammadiyah participates in handling Covid-19 by forming volunteers in a special team to prevent COVID-19 in every area, both urban and rural. In its implementation in the field, it was found that there were challenges, namely: (1) the lack of volunteers in handling patients indicated for COVID-19, (2) the fear of volunteers from transmitting the virus which could threaten them at any time, (3) the lack of assistance in terms of food due to a large number of patients, ( 4) lack of vaccine distribution, especially in remote villages, (5) the emergence of virus variants. Seeing this, Muhammadiyah responds and pays special attention to solutions, it is hoped that in the future in 2022 it will be better to handle the Covid-19 pandemic, including 1) strengthening the health system. Reinforcement of hospital networks and campaigns for healthy living needs to be continuously called for in a broad sense, 2) economic recovery, the Economic Council and Business Charities need to think about what needs to be done, 3) organize worship, 4) procurement of vaccines as an effort to overcome the new variant of Omicron from covid-19, and 5) making breakthroughs in dealing with the COVID-19 outbreak so that Muhammadiyah can survive with limited manpower and 6) postponement of the 48th congress until November 2022.